(untitled) (Journal of the College of Basic Education, 2022)
This study aimed to find out (the effect of using the generative learning model on the mathematical communication skills of fifth grade female students. The researcher selected fifth grade female students at Hani Bin Urwa School, and randomly chose (B) class as an experimental group (23) female students and (A) as a control group. (23) female students The generative learning model was applied to the experimental group in the chapters on ordinary fractions and operations on them Teaching plans were developed for both groups and a test in mathematical communication skills was built and the validity of the plan and test was found by presenting them to a group of arbitrators and specialists in mathematics and teaching methods and finding stability and coefficients Difficulty and discrimination coefficient of the test